Educar para emancipar: o direito do bebê à educação - Crucciti, Fernanda Jorge Kivitz (2021)
This research addressed the right of babies to education and analyzed the importance of integrating the education of children aged 0 to 3 years into care, understood in this research in its ethical and political dimension, so that care is the way to guarantee the baby's right to education. From this, and based on the fight for the baby's full right to education for public life from the cradle, we sought to offer contributions for reflection and the construction of an educational practice in Kindergarten schools, mainly to provide subsidies for the understanding of care in its ethical-educational dimension. The theoretical framework used in the field of Early Childhood Education in Brazil was Ângela Scalabrin Coutinho (2002, 2009, 2017, 2020), Fúlvia Rosemberg (1999, 2002, 2010), Maria Carmen Barbosa (2010), Maria Malta Campos (1999, 2007, 2008, 2009, 2013, 2014, 2018) and Zilma Moraes de Oliveira (1986, 1988, 2002, 2005, 2012); regarding the concept of care, Leonardo Boff (2006, 2013, 2014) and authors who discuss the concept of curricular justice were chosen: Branca Jurema Ponce (2009, 2015, 2017, 2019, 2020), Gimeno Sacristán (2013) and Jurjo Torres Santomé (2011, 2013). The methodology consisted of five steps: literature review; identification and reading of the texts of the authors who make up the theoretical references of this research on Early Childhood Education in Brazil; reading of official documents of the Ministry of Education that point out guidelines and parameters for Early Childhood Education; investigation of the history of childcare and Early Childhood Education in Brazil; reading of the literature on curricular justice – reference of analysis and horizon for a quality early childhood education school